2020
DOI: 10.1007/s10551-020-04517-1
|View full text |Cite
|
Sign up to set email alerts
|

Public Sector Organizational Failure: A Study of Collective Denial in the UK National Health Service

Abstract: This paper argues that public sector organizational failure may be best understood from a perspective of collective denial. The rise of this phenomenon is examined using testimony from a Public Inquiry into the downfall of a UK hospital, where falling organizational standards led to unethical decision making and an unacceptable number of patient deaths. In this paper we show how collective denial, over time, became a process that resided within the fabric of organizational life. To explore the organizational p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Therefore, Bourdieusian concepts of symbolic capital appear to have been reduced and misrepresented in practice among organisational improvement practitioners whose priorities are framed by narrowly defined metrics of profitability, risk avoidance or deflection and organisational productivity and efficiency (Ernst et al, 2018). The role of socio-cultural inequality within the workplace has often been re-framed as an area for individual intervention and increased personal resilience, rather than highlighting the need for wider organisational and systemic reform (Hendy and Tucker, 2020). We identified that certain staff groups appear to demonstrate a higher degree of confidence, comfort and intergroup support for speaking up even in the face of exposure to unprofessional behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Bourdieusian concepts of symbolic capital appear to have been reduced and misrepresented in practice among organisational improvement practitioners whose priorities are framed by narrowly defined metrics of profitability, risk avoidance or deflection and organisational productivity and efficiency (Ernst et al, 2018). The role of socio-cultural inequality within the workplace has often been re-framed as an area for individual intervention and increased personal resilience, rather than highlighting the need for wider organisational and systemic reform (Hendy and Tucker, 2020). We identified that certain staff groups appear to demonstrate a higher degree of confidence, comfort and intergroup support for speaking up even in the face of exposure to unprofessional behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Both these narratives had a moment of national glory. Similarly, Hendy and Tucker (2021) take collective denial as a concept that explains the public sector organization faults in the UK that led to failing standards and unethical decision making. Hendy and Tucker identify the presence of a “ narrative of silence .” This narrative allows failings to be justified through performance of national identity and organization loyalty by staff who have a distorted view on reality.…”
Section: Defenses In Large Groupsmentioning
confidence: 99%
“…So, Health care professionals should speak with patients and be aware about their cultural backgrounds, religious values and beliefs, thoughts, ethnic values, social norms and their stress and tensions ( 11 , 12 ). Because if professionals are not aware of blind spots, they may recommend treatments that are against a patient's wishes and lead to wrong and unethical decisions severely affect professional performance ( 11 , 14 ).…”
Section: Introductionmentioning
confidence: 99%